Ionic COFs nanosheet material based on carbon-carbon double bond connection, preparation method and water treatment membrane
By slowly growing on the surface of the template and removing the template by acid washing, the problems of irregular morphology and uneven size of covalent organic frame nanosheets were solved, and high-quality, uniform ionic COFs nanosheets were prepared for water treatment. The membrane exhibits excellent performance.
Patent Information
- Application Number
- CN202411183348.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2024-12-17
AI Technical Summary
The covalent organic frame nanosheets synthesized by traditional solvent-thermal synthesis have irregular morphology and are difficult to process, which limits their application fields. In addition, the COFs nanosheets synthesized by salt template-assisted single-phase solvothermal strategy are uneven in size and many impurity particles.
The preparation method of ionic COFs nanosheet material based on carbon-carbon double bond connection is adopted. The aromatic monomer is slowly grown on the surface of the template by using the phase transfer strategy to form a thin layer of COFs nanosheets, and the template is removed by acid washing to obtain high-quality Uniform ionic COFs nanosheets.
The processing of high-quality COFs nanosheets with uniform and controllable morphology and size is achieved, and the problems of irregular morphology and uneven dimensionality of traditional methods are overcome. It has good hydrophilicity and is suitable for the field of water treatment membranes.
Smart Images

Figure CN119143956A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer materials, and in particular to a preparation method and application of a covalent organic framework material. Background Art
[0002] Covalent organic frameworks (COFs) are constructed by periodically connecting organic building blocks through covalent bonds. They have attracted great interest due to their well-defined structure, high porosity, ordered pore structure, and strong structural and functional designability. However, most of the COFs synthesized by solvothermal methods are insoluble and infusible crystalline powders, which are difficult to process, greatly limiting their application areas. Compared with the morphology of irregular powders, nanosheets have very good processing characteristics. They can form dispersions and assemble into film devices through casting / filtration / doping, etc., and are widely used in optoelectronics, catalysis, water treatment, and gas separation. However, covalent organic framework nanosheets synthesized by traditional solvothermal strategies still have problems such as irregular morphology and difficult processing. Therefore, the synthesis of high-quality COFs nanosheets is extremely challenging. Summary of the invention
[0003] In order to solve the problem of synthesizing high-quality COFs nanosheets, the present invention provides an ionic COFs nanosheet material based on carbon-carbon double bonds, a preparation method, and a water treatment membrane. The method of the present invention uses a phase transfer strategy to grow a thin layer of COFs nanosheets on the template surface through the continuous and slow transfer of aromatic aldehyde monomers to the water phase, and the membrane assembled by the nanosheets shows excellent performance in the field of water treatment membranes.
[0004] The present invention is implemented by the following technical solutions:
[0005] (I) A method for preparing ionic COFs nanosheet materials based on carbon-carbon double bond connection
[0006] The preparation method comprises the following steps:
[0007] 1) preparing an aqueous solution containing an ionic COF building block and a catalyst and an oil solution containing an aromatic aldehyde building block;
[0008] 2) adding a template agent to the aqueous phase solution to obtain a template-aqueous phase solution;
[0009] 3) adding an oil phase solution onto the template-water phase solution to form an oil-water two-phase mixture, then sealing the reaction at the reaction temperature for a certain period of time, using a phase transfer strategy, and growing a thin layer of COFs on the template surface through the continuous and slow transfer of aromatic aldehyde building blocks to the water phase. After the reaction is completed, filtering and acid washing are performed to obtain the ionic COFs nanosheets.
[0010] Specifically, the ionic building blocks are one or more of the following molecular structures:
[0011]
[0012] Wherein, n is the length of the carbon chain in the ionic building block, n=0-9, that is, n is any integer between 0 and 9; X is one of the elements such as fluorine (F), chlorine (Cl), bromine (Br) and iodine (I).
[0013] Specifically, the catalyst is at least one of 4-methylaminopyridine and 4-dimethylaminopyridine.
[0014] Specifically, the template is at least one of water-insoluble inorganic salts such as calcium carbonate and magnesium carbonate.
[0015] Specifically, the aromatic aldehyde building blocks are one or more of the following molecular structures:
[0016]
[0017] Among them, m is the carbon chain length in the aromatic aldehyde building block, m=1~4, that is, m is any integer between 1 and 4; A is one of the elements or groups such as -H, -Br, -OCH3 and -OH, B is one of the elements or groups such as -H, -Br, -OCH3 and -OH, C is one of the elements or groups such as -H, -Br, -OCH3 and -OH, and D is one of the elements or groups such as -H, -Br, -OCH3 and -OH.
[0018] Specifically, in the step 1), the composition of the aqueous phase solution is: 0.1 to 500 mmol / L of ionic building blocks, 0.1 to 500 mmol / L of catalyst and the balance water; the composition of the oil phase solution is: 0.1 to 500 mmol / L of aromatic aldehyde building blocks and the balance organic solvent; the organic solvent is at least one of mesitylene, o-xylene and p-xylene.
[0019] Specifically, in the step 3), the reaction temperature is 120-210° C., and the reaction time is 1-7 days; that is, the reaction is carried out at a reaction temperature of 120-210° C. for 1-7 days, preferably at 160° C. for 3 days.
[0020] Specifically, in step 3), the pickling treatment uses at least one of hydrochloric acid, sulfuric acid and nitric acid solutions, preferably a hydrochloric acid solution.
[0021] Specifically, in the oil-water two-phase mixed liquid of step 3), the molar ratio of the ionic COF building blocks to the catalyst is 0.1:0.6-1.2, and the molar ratio of the ionic COF building blocks to the aromatic aldehyde building blocks is 1:0.5-1.5.
[0022] (II) An ionic COFs nanosheet material prepared by the above preparation method
[0023] (III) A water treatment membrane based on the above-mentioned ionic COFs nanosheet material
[0024] The water treatment membrane comprises a substrate and an ionic COFs nanosheet; the ionic COFs nanosheet adopts the above-mentioned ionic COFs nanosheet material.
[0025] The water treatment membrane is prepared by any of the following methods:
[0026] (a) Filtration self-assembly: vacuum filtration self-assembly of the solution of ionic COFs nanosheet material on a substrate such as polysulfone or nylon;
[0027] (b) Doping self-assembly: ionic COFs nanosheet materials are incorporated into traditional polyamide separation layers.
[0028] The method for preparing ionic COFs nanosheet materials provided by the present invention utilizes a two-phase solvothermal strategy assisted by a salt template, and slowly and continuously transfers an oil-phase aromatic aldehyde monomer to a water phase, so that in-situ thin-layer growth of ionic COFs nanosheets on the surface of an inorganic salt can be achieved. The salt template is subsequently removed by acid washing to obtain high-quality, uniform ionic COFs nanosheets, thereby overcoming the problems of irregular morphology and difficult processing of COFs synthesized by a traditional solvothermal strategy, and also overcoming the problems of uneven size and many impurity particles of COFs nanosheets synthesized by a single-phase solvothermal strategy assisted by a salt template.
[0029] The beneficial effects of the present invention are as follows:
[0030] 1. The method for preparing the ionic COFs nanosheet material of the present invention can prepare the ionic COFs nanosheet material with uniform and controllable morphology and size, thereby realizing high-quality processing of the ionic COFs nanosheet material.
[0031] 2. The preparation method of the ionic COFs nanosheet material in the present invention has the characteristics of simple preparation process and easy industrial scale-up.
[0032] 3. The ionic COFs nanosheet material prepared by the method of the present invention contains ionized groups, and therefore not only has the advantages of large size, high quality and uniformity, but also has good hydrophilicity, and has great practical application prospects in the field of water treatment membranes. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a flow chart of the method for preparing ionic COFs nanosheets provided in Example 1 of the present invention.
[0034] Figure 2 This is a scanning electron microscope image of ionic thin layer COFs grown on the surface of the salt template in Example 1 of the present invention.
[0035] Figure 3 are morphology pictures of the ionic COFs nanosheets in the present invention; (A) is the morphology picture of the ionic COFs nanosheets in comparative example 1 of the present invention, (B) is the morphology picture of the ionic COFs nanosheets in comparative example 2 of the present invention, (C) is the morphology picture of the COFs nanosheets after acid washing to remove the salt template in Example 1 of the present invention, and (D) is the morphology picture of the COFs nanosheets after acid washing to remove the salt template in Example 1 of the present invention.
[0036] Figure 4 This is the XRD diagram of the ionic COFs nanosheets in Example 2 of the present invention.
[0037] Figure 5 Surface and cross-sectional morphologies of the composite membrane formed by self-assembly through suction filtration in Example 5 of the present invention. DETAILED DESCRIPTION
[0038] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] The present invention provides a method for preparing an ionic COFs nanosheet material based on carbon-carbon double bond connection. The process of the preparation method of the present invention is as follows Figure 1 As shown, the method of the present invention first configures the ionic COF building blocks and the catalyst into an aqueous solution, and adds a template to the aqueous solution; then, an oil phase solution containing aromatic aldehyde building blocks is added above the aqueous phase to form an oil-water two-phase mixed solution; the reaction is sealed for a certain time under heating conditions at a certain temperature, and a thin layer of COFs is grown on the template surface by the aromatic aldehyde monomers continuously and slowly transferring to the aqueous phase using a phase transfer strategy; the template is subsequently removed by acid washing to obtain ionic COFs nanosheets. Such ionic COFs nanosheets have large size, high quality and uniformity, and can be further prepared into composite separation membranes through self-assembly strategies such as filtration / doping.
[0040] The thickness of the thin-layer ionic COFs nanosheet material obtained by the method of the present invention can reach 0.9 nm to 5 nm.
[0041] Furthermore, in a specific implementation, the planar dimensions, ie, the length and width dimensions, of the ionic COFs nanosheet material can be controlled by changing the size of the template particles.
[0042] Furthermore, the present invention also provides a composite separation membrane prepared based on the above-mentioned ionic COFs nanosheet material. The composite separation membrane is prepared by vacuum filtration self-assembly of ionic COFs nanosheets on a substrate such as polysulfone or nylon, or by incorporating ionic COFs nanosheets into a traditional polyamide separation layer. The composite membrane can be used for water treatment applications.
[0043] Example 1
[0044] Weigh N-sulfopropyl-2,4,6-trimethylpyridine (0.3mmol) and 4-dimethylaminopyridine (1.8mmol), dissolve in 2mL water, add 120-mesh calcium carbonate template, dissolve 4,4'-biphenyldicarboxaldehyde (0.45mmol) in 20mL mesitylene and add the above aqueous phase, and seal and react at 150°C for 3 days. After the reaction is completed, filter to obtain calcium carbonate particles with a thin layer of COFs on the surface, wash with a 2mol / L hydrochloric acid (HCl) solution to remove the calcium carbonate template, then wash and filter with pure water, tetrahydrofuran, and ethanol solvents in turn, and dry to obtain ionic COFs nanosheets.
[0045] Figure 2 This is a scanning electron microscope image of the growth of ionic thin-layer COFs on the surface of the salt template (calcium carbonate template) in this embodiment. Figure 2 It can be seen that the surface of calcium carbonate is covered with a thin layer of COFs.
[0046] Figure 3 Figure 3 is a morphology diagram of the ionic COFs nanosheets in the present invention. Figure 3 (C) and Figure 3 As can be seen from (D), the ionic COFs after acid washing to remove the template show typical nanosheet morphology characteristics, and the morphology and size are uniform.
[0047] Compared with Example 1, the COFs powder obtained in Comparative Example 1 has an irregular morphology ( Figure 3 In Comparative Example 2, although the salt template effect was partially achieved, there was still a competitive solution homogeneous nucleation-growth-crystallization process to form COF powder. Therefore, the COFs nanosheets obtained in Comparative Example 2 were of uneven size and contained a large number of impurity particles ( Figure 3 (B)).
[0048] The thickness of the ionic COFs obtained in this embodiment is about 0.9 nm to 5 nm, and the length and width are both in the micrometer level.
[0049] Example 2
[0050] N-ethyl-2,4,6-trimethylpyridinium bromide (0.3 mmol) and 4-dimethylaminopyridine (1.8 mmol) were weighed and dissolved in 2 mL of water, and a 120-mesh calcium carbonate template was added. 3,3'-dimethoxy-[1,1'-biphenyl]-4,4'-dicarboxaldehyde (0.45 mmol) was dissolved in 40 mL of mesitylene and then added to the above aqueous phase. The mixture was sealed and reacted at 160°C for 3 days. The calcium carbonate particles with a thin layer of COFs on the surface were filtered to obtain the calcium carbonate particles. The calcium carbonate template was washed with a 2 mol / L hydrochloric acid (HCl) solution to remove the calcium carbonate template, and then washed and filtered with pure water, tetrahydrofuran, and ethanol solvents in turn, and dried to obtain ionic COFs nanosheets.
[0051] Figure 4 This is the XRD pattern of ionic COFs nanosheets after acid washing, showing good crystallinity.
[0052] In order to further verify the feasibility of assembling COFs nanosheets into composite membranes, a composite separation membrane was prepared by vacuum filtration self-assembly using the COFs nanosheets obtained in Example 1.
[0053] Embodiment 3 to Embodiment 5
[0054] The COFs nanosheets obtained in Example 1 were dispersed with pure water, further centrifuged at 2000 rpm and the supernatant was taken. A COFs nanosheet aqueous dispersion mother liquor with a concentration of 0.092 mg / mL was obtained. Then 2.5 mL (Example 3), 5 mL (Example 4), and 10 mL (Example 5) of the mother liquor were measured respectively, and further diluted with water to 20 mL of solution. The COFs nanosheets obtained in Example 1 were deposited on a nylon base filter membrane by vacuum filtration self-assembly, and then dried at room temperature for 12 hours to obtain a composite membrane.
[0055] Figure 5 The surface (left) and cross-sectional (right) morphologies of the composite membrane formed by suction filtration self-assembly in Example 5 show that the surface of the composite membrane is a dense, defect-free separation cortex.
[0056] The separation performance of the composite membranes in Examples 3 to 5 is shown in the following table:
[0057]
[0058] It can be seen that the composite membranes in Examples 3 to 5 all exhibited excellent water permeability and dye removal rate. It can be seen that the composite membrane prepared based on the ionic COFs nanosheet material in the present invention exhibits excellent separation performance in the field of water treatment.
[0059] Comparative Example 1
[0060] Weigh N-sulfopropyl-2,4,6-trimethylpyridine (0.3 mmol), 4-dimethylaminopyridine (1.8 mmol), and 4,4'-biphenyldicarboxaldehyde (0.45 mmol) and disperse them in a mixed solution of o-dichlorobenzene / n-butanol / water (3 mL / 3 mL / 0.6 mL). Seal the solution and react at 150 °C for 3 days. Then wash and filter with pure water, tetrahydrofuran, and ethanol solvents in turn, and dry to obtain ionic COFs powder.
[0061] Comparative Example 2
[0062] Weigh N-sulfopropyl-2,4,6-trimethylpyridine (0.3 mmol) and 4-dimethylaminopyridine (1.8 mmol), 4,4'-biphenyldicarboxaldehyde (0.45 mmol) and disperse them in a mixed solution of o-dichlorobenzene / n-butanol / water (3 mL / 3 mL / 0.6 mL), add calcium carbonate template, and then seal and react at 150 ° C for 3 days. After the reaction is completed, filter the reaction product, remove the template with a 2 mol / L hydrochloric acid solution, wash and filter with pure water, tetrahydrofuran, and ethanol solvents in turn, and dry to obtain ionic COFs nanosheets.
[0063] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing an ionic COFs nanosheet material based on carbon-carbon double bond connection, characterized in that: The preparation method comprises the following steps: 1) preparing an aqueous solution containing an ionic COF building block and a catalyst, and an oil solution containing an aromatic aldehyde building block; 2) adding a template agent to the aqueous phase solution to obtain a template-aqueous phase solution; 3) adding an oil phase solution onto the template-water phase solution to form an oil-water two-phase mixed solution, and then sealing and reacting at a reaction temperature. After the reaction is completed, filtering and acid washing are performed to obtain the ionic COFs nanosheets.
2. The method for preparing an ionic COFs nanosheet material based on carbon-carbon double bond connection according to claim 1, characterized in that: The ionic building blocks are one or more of the following molecular structures: Wherein, n=0-9, and X is one of fluorine, chlorine, bromine and iodine.
3. The method for preparing an ionic COFs nanosheet material based on carbon-carbon double bond connection according to claim 1, characterized in that: The catalyst is at least one of 4-methylaminopyridine and 4-dimethylaminopyridine.
4. The method for preparing an ionic COFs nanosheet material based on carbon-carbon double bond connection according to claim 1, characterized in that: The template is at least one of calcium carbonate and magnesium carbonate.
5. The method for preparing an ionic COFs nanosheet material based on carbon-carbon double bond connection according to claim 1, characterized in that: The aromatic aldehyde building blocks are one or more of the following molecular structures: Among them, m=1~4, A is one of -H, -Br, -OCH3 and -OH, B is one of -H, -Br, -OCH3 and -OH, C is one of -H, -Br, -OCH3 and -OH, and D is one of -H, -Br, -OCH3 and -OH.
6. The method for preparing an ionic COFs nanosheet material based on carbon-carbon double bond connection according to claim 1, characterized in that: In the step 1), the composition of the aqueous phase solution is: 0.1-500 mmol / L of ionic building blocks, 0.1-500 mmol / L of catalyst and the balance of water; the composition of the oil phase solution is: 0.1-500 mmol / L of aromatic aldehyde building blocks and the balance of organic solvent; the organic solvent is at least one of mesitylene, o-xylene and p-xylene.
7. The method for preparing an ionic COFs nanosheet material based on carbon-carbon double bond connection according to claim 1, characterized in that: In the step 3), the reaction temperature is 120-210° C. and the reaction time is 1-7 days.
8. The method for preparing an ionic COFs nanosheet material based on carbon-carbon double bond connection according to claim 1, characterized in that: In the oil-water two-phase mixed liquid of step 3), the molar ratio of the ionic COF building blocks to the catalyst is 0.1:0.6-1.2, and the molar ratio of the ionic COF building blocks to the aromatic aldehyde building blocks is 1:0.5-1.
5.
9. An ionic COFs nanosheet material prepared by the preparation method according to any one of claims 1 to 8.
10. A water treatment membrane, characterized in that: The water treatment membrane comprises a substrate and an ionic COFs nanosheet; the ionic COFs nanosheet is made of the ionic COFs nanosheet material as claimed in claim 9, and the water treatment membrane is prepared by any one of the following methods: (a) Vacuum filtration of ionic COFs nanosheets on a substrate; (b) Incorporation of ionic COFs nanosheet materials into the polyamide separation layer.
